The Effect of Green Accounting on Company Reputation as a Moderating Variable for Corporate Governance - Rifi Rafita Sari; Desi Ilona; Yuli Ardiany (Jurnal Riset Akuntansi, 2025)
This study aims to determine the effect of green accounting on company reputation with corporate governance as a moderating variable. The population in this research is manufacturing companies in the materials and energy sub-sector, totaling 35 companies. The type of research used is secondary data. The test results show that green accounting partially has a positive and significant effect on company reputation. Meanwhile, corporate governance partially has no significant effect on company reputation. And corporate governance as a moderating variable partially has a negative and significant effect in moderating and weakening the relationship between green accounting and corporate reputation in manufacturing companies in the materials and energy sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period.